PENYULUHAN SERTA TATA LAKSANA PENYAKIT HIPERTENSI DAN KARDIOVASKULAR BAGI MASYARAKAT DUSUN DADUNG DESA SAMBIREJO NGAWI JAWA TIMUR - Sawitri, Satwika Budi; Dewi, Mahmud Carica; Ramadhani, Della; Arsy, Isabel; Said, Najwa; Azizah, Wafiq Nur (Jurnal Abdimas Kesehatan (JAKes), 2025)
The risk of hypertension increases progressively with age. The urgency to prevent further complications by providing appropriate information and management will improve the quality of life of patients with hypertension. The goal of this community service activity is to improve management and adherence to therapy, as well as changes to a healthy lifestyle to control blood pressure. This activity method involves counseling and education on hypertension management in the community. This can be implemented by providing education and distributing leaflets or brochures, making it easier for patients to recognize their disease and lifestyle control to improve their quality of life. Counseling can be done through presentations, while we carried out education and information by distributing leaflets to the Dadung hamlet community through the PKK women's group. The results of this activity, which implemented a community-based hypertension education program, have been proven to lower blood pressure and improve medication adherence. Promotional and preventive efforts for non-communicable diseases need to be continuously developed and supported by adequate policies. Counseling and education on hypertension aim to increase public knowledge about this disease, including risk factors, prevention, and the importance of regular treatment. Previous research has shown that providing health information directly by pharmacists can improve patient compliance in taking medication and maintaining blood pressure control. The conclusion of this community service activity is that a community-based hypertension education program has been proven to lower blood pressure and improve medication adherence. The education and counseling on hypertension aims to increase public knowledge about the disease, including risk factors, prevention, and the importance of regular medication.